Proposed form on Accountant Disclosure About the Social Responsibility in Financial Reports and Lists for Economic Units - Mohammed Rafeeq Mustafa (QALAAI ZANIST SCIENTIFIC JOURNAL, 2019)
Contemporary accounting disclosure seeks to meet the information needs of the owners of the economic unit and all beneficiaries of the financial statements, whether these categories are internal or external, and the importance of the research comes from the need to identify the nature of social contributions to economic unity and the benefits it provides and the social and environmental damage it causes to members of society. For the purpose of identifying this, the research will attempt to indicate the methods of accounting disclosure that can be used in preparing information that expresses social responsibility and that can be disclosed in the financial statements of the various denominations of the beneficiaries. Readers of the financial statements are beneficiaries of the social responsibility of the unit, so the researcher suggested an accounting model that can help in dealing with this problem. The research is based on several hypotheses, the most important of which is that interest in accounting disclosure for social responsibility would contribute to improving the results of activity for economic unity and revealing its practical reality from a social angle. The research has concluded with a set of results, the most important of which is that the difficulties facing the accounting disclosure of social responsibility information is the lack of a unified method for presenting social responsibility information, in addition to the fact that most of the outputs of social activities in economic units, whether financial or quantitative, affect expenditures, obligations and assets of unity And its management decisions that are a matter of disclosure are among the core of accounting work.